El ordenamiento territorial: instrumento para la gobernabilidad (2005)
The issue of territorial ordinance should be conceived as a tool to favoring the democratic and institutional governing of the country In this sense, it become necessary to rethink the ordinance issue beyond traditional figures of territorial organization, which would allow to restructure and llexibilize the integration and performance processes within the territory The 1991 Constitution lett an opening for many territorial organization possibilities which are vet to be developed by the Colombian Legislature through the Organic Law of Territorial Ordinance. The project of the organic law underway in the Congress reproduce- the model already existing in the legal norms, and does not develop the mandates of autonomy, equity, and territorial flexibility that are in the Constitution.